Successful Use of Entecavir in Hepatitis B-associated Membranous Nephropathy. (27th July 2017) - Mahajan, Vidushi; D'Cruz, Sanjay; Nada, Ritambara; Sachdev, Atul
Abstract: We report the case of a 7-year-old unimmunized boy who presented with generalized anasarca for the first time, along with nephrotic-range proteinuria, hypoalbuminemia, microscopic hematuria and hypertension. Special investigations revealed ELISA test to be positive for hepatitis B surface antigen (HBsAg) and hepatitis B envelope antigen (HBeAg); hepatitis B viral DNA load (HBV DNA) level (real-time polymerase chain reaction) was 54 360 903 IU/ml. For hepatitis B virus (HBV)-related glomerulopathy, he was started on enalapril and lasilactone, and percutaneous renal biopsy was performed, which revealed membranous nephropathy (MN). A diagnosis of MN secondary to HBV infection contracted via horizontal transmission was made. The patient was started on peginterferon alfa-2b (50 μg/week) for 24 weeks. He failed to attain remission and seroconversion after interferon (IFN) therapy. Then, oral therapy with entecavir was started, and he attained remission as well as seroconversion after 3 months of therapy. He maintained his seroconversion status at his 6-month and the recent 12-month (quantitative HBV DNA level was 373 IU/ml) follow-up visit. Entecavir seems a promising drug for HBV-related glomerulopathy, especially in IFN-resistant cases.